PENYULINGAN KULIT MASOI (CINNAMOMUM XANTHONEURON BL) BAGIAN 1 (Distillation of Masoi bark (Cinnamomum xanthoneuron BL.). Part I) PENGARUB CARA DAN WAKTU PENYULINGAN KULIT MASOI (The effect of distilling method and time) - Abdul Hakim Lukman; Bambang Wiyono; Poedji Hestoeti (Jurnal Penelitian Hasil Hutan, 1991)
This  paper  describes  a preliminary  experiment  on the effect of dilstillation method  and  time on  yield of  The methods  applied   were cohobation and water-steam   method  with distilling  times of 3, 9, 18, 30 and 36 hours, consecutivety. The result   shows  that  the distilling time and method appears  to have a highly  significant effect on oil yisld and the cohobation methad produces higher oil yield compared with water-steam distillation.